Fatty acid compositions of triglycerides and free fatty acids in sebum depend on amount of triglycerides, and do not differ in presence or absence of acne vulgaris. Issue 12 (12th November 2014) - Akaza, Narifumi; Akamatsu, Hirohiko; Numata, Shigeki; Matsusue, Miyuki; Mashima, Yasuo; Miyawaki, Masaaki; Yamada, Shunji; Yagami, Akiko; Nakata, Satoru; Matsunaga, Kayoko
Abstract To clarify the influence of the fatty acid composition of sebum in acne vulgaris, we investigated the amounts and fatty acid compositions of triglycerides (TG) and free fatty acids (FFA), and the amounts of cutaneous superficial Propionibacterium acnes in acne patients and healthy subjects. The foreheads of 18 female patients, 10 male patients, 10 healthy females and 10 healthy males were studied in a Japanese population. There were significant differences in the amounts of sebum, TG and cutaneous superficial P. acnes, as well as the fatty acid compositions of TG and FFA between acne patients and healthy subjects in females. Their fatty acid compositions were correlated with the amount of TG with or without acne. It was clarified that the fatty acid compositions of TG and FFA depended on the amount of TG, and there were no differences in the fatty acid composition in the presence and absence of acne.